Standardization of multiplex PCR for identification of ten staphylococci species and their prevalence in bovine mastitis - SHAFI, TAWHEED AHMAD; BANSAL, BALJINDER KUMAR; SHARMA, SHUKRITI; SHARMA, NARINDER SINGH (The Indian Journal of Animal Sciences, 2022)
To assess the clinical impact, epidemiology of intra-mammary infections, accurate diagnosis, and choosingappropriate antimicrobial therapy, the staphylococci group should be studied correctly up to the species level. Inthis study, a multiplex PCR (mPCR) was developed to identify 10 important Staphylococcus species that wasapplied to study the prevalence of staphylococci species in bovine mastitis from five agro-climatic regions ofPunjab, India. A two tube mPCR assay consisted of 5 species each, with one reaction including primer pairs ofS. epidermidis, S. hemolyticus, S. hominis, S. warneri and S. saprophyticus, and another reaction consisted primerpairs of S. aureus, S. intermedius, S. chromogenes, S. sciuri and S. capitis was standardized. Prevalence studyrevealed S. aureus (35.76%) as most prevalent species among all staphylococci followed by S. chromogenes (16.56%),S. haemolyticus (15.23%), S. epidermidis (5.30%), S. sciuri (1.99%), S. capitis (0.66%), S. hominis (0.66%),S. saprophyticus (0.66%) and rest were other staphylococci (23.18%). The mPCR developed in this study could beused for identification of staphylococci of various origins including those from human specimens. The high prevalenceof S. chromogenes and S. haemolyticus in the present study suggest emergence of these non-aureus staphylococciin bovine mastitis in Punjab (India).